Microbiome of athletes: Its features and diversity: A literature review - Palladina, O.; Kaliga, A. (International Journal of Medicine and Medical Research, 2024)
The microbiome of athletes is of the greatest interest among researchers, as the microbial composition of the colon plays a key role in the absorption of nutrients, the synthesis of vitamins, and the immune response of the host body. The purpose of this review was to investigate the relationship between the gut microbiota in high-performance athletes and people with low-activity lifestyles, and the effect of these changes on the production of microbial metabolites that are associated with physical performance and athletic performance of athletes. A total of 42 research papers were analysed, including 11 specialised studies that examined the effect of intense physical activity of different types on the microbial composition of the gut and 19 studies that focused on the correlation of individual bacteria and physical performance. Gut microbial composition has been found to be associated with athletic performance and is likely to improve performance and recovery. Physical activity has been shown to increase a-diversity and microbial metabolites, such as short-chain fatty acids, compared to people who have a low-activity lifestyle. There were no significant differences in a-diversity between sports. The microbiome of athletes was characterised by a higher amount of short-chain fatty acids, which can be energy substrates during exercise. The production of short-chain fatty acids is associated with Eubacterium rectale, Blautia spp., Faecalibacterium prausnitzii. The athletes` microbiome also demonstrated the presence of Prevotella spp., which in athletes may correlate with performance. It has been shown that the presence of Veillonella atypica in athletes positively correlates with endurance. Despite the fact that the findings are contradictory, sports achievements and health of athletes specialising in various sports are associated with such types of bacteria as Akkermansia municiphila, Faecalibacterium prausnitzii, Eubacterium rectale, Roseburia hominis. In addition, it has been shown that there is a link between the microbial composition of the gut and enzymes that are considered key in the production of metabolites associated with the health of athletes